Two DsbA Proteins Are Important for Vibrio parahaemolyticus Pathogenesis - Wu, Chun-qin; Zhang, Ting; Zhang, Wenwen; Shi, Mengting; Tu, Fei; Yu, Ai; Li, Manman; Yang, Menghua (Frontiers in Microbiology, 2019)
Bacterial pathogens maintain disulfide bonds for protein stability and functions that are required for pathogenesis. Vibrio parahaemolyticus is a Gram-negative pathogen that causes food-borne gastroenteritis and is also an important opportunistic pathogen of aquatic animals. Two genes encoding the disulfide bond formation protein A, DsbA, are predicted to be encoded in the V. parahaemolyticus genome. DsbA plays an important role in Vibrio cholerae virulence but its role in V. parahaemolyticus is largely unknown. In this study, the activities and functions of the two V. parahaemolyticus DsbA proteins were characterized. The DsbAs affected virulence factor expression at the post-translational level. The protein levels of adhesion factor VpadF (VP1767) and the thermostable direct hemolysin (TDH) were significantly reduced in the dsbA deletion mutants. V. parahaemolyticus lacking dsbA also showed reduced attachment to Caco-2 cells, decreased β-hemolytic activity, and less toxicity to both zebrafish and HeLa cells. Our findings demonstrate that DsbAs contribute to V. parahaemolyticus pathogenesis.